2021
DOI: 10.1136/bmjgh-2020-004181
|View full text |Cite
|
Sign up to set email alerts
|

Cost and cost-effectiveness of a real-world HCV treatment program among HIV-infected individuals in Myanmar

Abstract: IntroductionOver half of those hepatitis C virus (HCV)/HIV coinfected live in low-income and middle-income countries, and many remain undiagnosed or untreated. In 2016, Médecins Sans Frontières (MSF) established a direct-acting antiviral (DAA) treatment programme for people HCV/HIV coinfected in Myanmar. The purpose of our study was to evaluate the real-world cost and cost-effectiveness of this programme, and potential cost-effectiveness if implemented by the Ministry of Health (MoH).MethodsCosts (patient-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…There is increasing evidence that scaling up HCV treatment is highly cost-effective and potentially cost-saving in a number of settings. Subnational studies in various LMICs have shown DAA treatment of HCV-diagnosed patients to be cost-effective in Myanmar [ 47 ] and cost-saving in India, Thailand, and South Africa, but they did not include screening costs [ 48 ]. Other subnational studies in Egypt [ 49 ], Cambodia [ 6 ], and Pakistan [ 21 ] have shown that screening and DAA treatment can be cost-effective or possibly cost-saving when compared to no screening and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that scaling up HCV treatment is highly cost-effective and potentially cost-saving in a number of settings. Subnational studies in various LMICs have shown DAA treatment of HCV-diagnosed patients to be cost-effective in Myanmar [ 47 ] and cost-saving in India, Thailand, and South Africa, but they did not include screening costs [ 48 ]. Other subnational studies in Egypt [ 49 ], Cambodia [ 6 ], and Pakistan [ 21 ] have shown that screening and DAA treatment can be cost-effective or possibly cost-saving when compared to no screening and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Within Myanmar, MSF proposed a simplified model of HCV care to the Myanmar Ministry of Health, which incorporated fewer patient visits, task-shifting from doctors to nurses and using local staff, and was estimated to be highly costeffective (ICER <USD400/DALY averted compared with no treatment in HCV/HIV coinfected patients). 31 We used WHO-prequalified generic DAAs ordered and imported via pooled procurement, so our DAA price was lower than private clinics in Myanmar (SOF/DCV price USD399 (2018) to USD330 (2019) for 12-week treatment versus USD86.76 for 12-week treatment in CT2). Therefore, we conducted sensitivity analyses for 12-week treatment prices of USD300, 20 USD150 based on the DAA prices in Myanmar, and USD28 (from a neighboring country [Pakistan]), 10 finding that the CT2 model of care had a 90% probability of being costeffective if measured against a willingness-to-pay thresholds of 60%, 30%, or 12% per capita GDP respectively (see Appendix).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with other studies regarding the cost‐effectiveness of HCV testing and treatment in LMICs that have shown treating HCV with generic DAAs is cost‐effective 28–30 . Within Myanmar, MSF proposed a simplified model of HCV care to the Myanmar Ministry of Health, which incorporated fewer patient visits, task‐shifting from doctors to nurses and using local staff, and was estimated to be highly cost‐effective (ICER <USD400/DALY averted compared with no treatment in HCV/HIV coinfected patients) 31 …”
Section: Discussionmentioning
confidence: 99%
“…La terapia para hepatitis C crónica en pacientes VIH-positivos es costo-efectiva (19) , por lo que todos los pacientes deberían ser tratados oportunamente y en serie, inde-pendientemente del estadio de fibrosis hepática. Para ello, se requiere un esfuerzo y organización real de los programas de VIH; pero aun eso no será suficiente.…”
Section: Discussionunclassified